Comparative Analyses of Fecal Microbiota in European Mouflon (Ovis orientalis musimon) and Blue Sheep (Pseudois nayaur) Living at Low or High Altitudes - Sun, Guolei; Zhang, Honghai; Wei, Qinguo; Zhao, Chao; Yang, Xiufeng; Wu, Xiaoyang; Xia, Tian; Liu, Guangshuai; Zhang, Lei; Gao, Ying; Sha, Weilai; Li, Ying (Frontiers in Microbiology, 2019)
The gut microbiota is a complex and essential system organ that plays an integrative role in balancing key vital functions in the host. Knowledge of the impact of altitude on the gut microbiota of European mouflon (Ovis orientalis musimon) and blue sheep (Pseudois nayaur) is currently limited. In this study, we compared the characteristics of gut microbiota in 5mouflon at low altitude (K group),4 mouflon at high altitude (L group),4 blue sheep at low altitude (M group)and 4 blue sheep at high altitude (N group). The V3–V4 region of the 16S rRNA gene was analyzed using high-throughput sequencing. Analyses based on the operational taxonomic units showed significant changes in the gut microbial communities between groups at different altitudes. At the phylum level, groups at the high altitudes had a higher relative abundance of Firmicutes and a lower relative abundance of Bacteroidetes than those at the low altitudes. A higher Firmicutes:Bacteroidetes ratio is beneficial to animals in terms of the gut microbiota-mediated energy harvest. The relative abundance of Proteobacteria was significantly higher in the gut microbiota of mouflon sheep at high altitudes. At the genus level, the Bacteroides:Prevotella ratio was significantly higher in the low-altitude group (than the high-altitude group) of mouflon sheep and the ratio was significantly higher in the high-altitude group (than the low-altitude group) in blue sheep. In addition, the Ruminococcaceae_UCG-005 related to cellulose and starch digestion was the predominant genus in blue sheep and the relative abundance of the genus was significant higher in the high-altitude group than the low-altitude group of blue sheep (P<0.01). In conclusion, our results suggested that the gut microbiota of high-altitude groups of sheep had stronger abilities related to energy metabolism and the decomposition of substances, e.g., fiber and cellulose, and that such abilities are associated with high-altitude adaptation.